How to avoid being re-hospitalized for patients with COVID-19 - Li Shi; Jie Chen; Jiqing He (Open Journal of Tropical Medicine - Peertechz Publications, 2021)
Aim: How to avoid being re-hospitalized for patients with 2019 Novel Coronavirus (COVID-19) were studied.  Method: A total of 260 patients diagnosed as COVID-19 were studied with serial follow-up chest chest Computed Tomography (CT) scans and Reverse-Transcriptase-Polymerase-Chain-Reaction (RT-PCR).  Result: Positive rates of chest CT imaging were 96.99% (252/260). Positive rates of RT-PCR were 87.70% for the first time, 92.30% for two times and 100% for three times. Multiple RT-PCR assay tests resulted in a high positive rate of RT-PCR. Combination of chest CT scans, RT-PCR lead to positive rate of 100% even for the first testing, which is conducive to COVID-19 diagnosis Two patients with COVID-19 were discharged from hospital with false-negative results of RT-PCR using the oropharyngeal swab. There was a significant progression on CT images as well as an increase in infective markers during their second admission to hospital, which indicated the progressing inflammation. Patients with complete recovery were selected. Symptoms were relieved; dissipation almost completely disappeared on CT image; infective markers significantly decreased to normal levels, which indicated that the inflammation was not progressing. Lymphocyte (LYM) percent increase to normal level.  Conclusion: Serial follow-up chest CT scans are quite important for confirming the patients with COVID-19 who resulted negative for RT-PCR of COVID-19 nucleic acid. A combination of the RT-PCR test for COVID-19 nucleic acid and other detective methods such as CT imaging are conducive to diagnosis. The roadmap how to avoid being re-hospitalized for patients with COVID-19 was provided. Patients, were not allowed to be discharged from hospital even with negative result of RT-PCR of COVID-19 nucleic acid: